Hyperspectral Imaging Provides Early Prediction of Random Axial Flap Necrosis in a Preclinical Model. Issue 6 (June 2017) - Chin, Michael S.; Chappell, Ava G.; Giatsidis, Giorgio; Perry, Dylan J.; Lujan-Hernandez, Jorge; Haddad, Anthony; Matsumine, Hajime; Orgill, Dennis P.; Lalikos, Janice F.
Abstract : Background: Necrosis remains a significant complication in cutaneous flap procedures. Monitoring, and ideally prediction, of vascular compromise in the early postoperative period may allow surgeons to limit the impact of complications by prompt intervention. Hyperspectral imaging could be a reliable, effective, and noninvasive method for predicting flap survival postoperatively. In this preclinical study, the authors demonstrate that hyperspectral imaging is able to correlate early skin perfusion changes and ultimate flap survival in a preclinical model. Methods: Thirty-one hairless, immunocompetent, adult male mice were used. Random pattern dorsal skin flaps were elevated and sutured back into place with a silicone barrier. Hyperspectral imaging and digital images were obtained 30 minutes, 24 hours, or 72 hours after flap elevation and before sacrifice on postoperative day 7. Results: Areas of high deoxygenated hemoglobin change (124; 95 percent CI, 118 to 129) seen at 30 minutes after surgery were associated with greater than 50 percent flap necrosis at postoperative day 7. Areas demarcated by high deoxygenated hemoglobin at 30 minutes postoperatively had a statistically significant correlation with areas of macroscopic necrosis on postoperative day 7. Analysis of images obtained at 24 and 72 hours did not show similar changes. Conclusions: These findings suggest that early changes in deoxygenated hemoglobin seen with hyperspectral imaging may predict the region and extent of flap necrosis. Further clinical studies are needed to determine whether hyperspectral imaging is applicable to the clinical setting.